Preliminary considerations on the genesis of the “social issue” in Brazil - Bruinjé, Ana Luíza Tavares (Argumentum, 2024)
The article analyses the contributions of Jacob Gorender and Clóvis Moura to the understanding the genesis of the “social issue” in the specific circumstances of Brazil. It highlights work, State, and class struggle as essential categories for investigating the “social issue”; and, race and class as irreducible categories of the Brazilian reality. From this analysis, we demonstrate that the fundamental determinants that established the general conditions of the “social issue” in Brazil were formed during the historical process of transition from slave labour to salaried labour between 1850 and 1930.